Prescribing Pattern of Antibiotics in Paediatric Inpatients of Bakulahar Ratnanagar Hospital, Chitwan (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: The rational use of antibiotics is crucial in paediatric healthcare settings to mitigate the risk of antimicrobial resistance. This study aimed to assess the prescription patterns of antibiotics among paediatric inpatients at Bakulahar Ratnanagar Hospital, Ratnanagar, Chitwan.MATERIALS AND METHODS:  A cross-sectional study conducted over a 2-month period in May-June 2023 involved the analysis of 160 patient case sheets from the paediatric inpatient department. Patients with various infections were included, and data were analyzed using SPSS.RESULTS: The mean age of paediatric patients was 2.83 years. Each encounter involved an average of 3.4 drugs, with 1.86 antibiotics per patient. Pneumonia emerged as the most prevalent disease. Among antibiotics, the Cephalosporin group, particularly Ceftriaxone and Cefotaxime, were frequently prescribed. The combination antibiotic Ceftriaxone plus Tazobactam was widely used.CONCLUSIONS: Strict adherence to antibiotic prescription policies can significantly curb overuse and reduce antibiotic resistance development.